Molecular epidemiological survey of porcine epidemic diarrhea in some areas of Shandong and genetic evolutionary analysis of S gene - Shen, Yesheng; Yang, Yudong; Zhao, Jun; Geng, Ningwei; Liu, Kuihao; Zhao, Yiran; Wang, Fangkun; Liu, Sidang; Li, Ning; Meng, Fanliang; Liu, Mengda (Frontiers in Veterinary Science, 2022)
Responsible for the acute infectious disease porcine epidemic diarrhea (PED), PED virus (PEDV) induces severe diarrhea and high mortality in infected piglets and thus severely harms the productivity and economic efficiency of pig farms.In our study, we aimed to investigate and analyze the recent status and incidence pattern of PEDV infection in some areas of Shandong Province, China.We collected 176 clinical samples of PED from pig farms in different regions of Shandong Province during 2019–2021. PEDV, TGEV, and PORV were detected using RT-PCR. The full-length sequences of positive PEDV S genes were amplified, the sequences were analyzed with MEGA X and DNAStar, and a histopathological examination of typical PEDV-positive cases was performed. RT-PCR revealed positivity rates of 37.5% (66/176) for PEDV, 6.82% (12/176) for transmissible gastroenteritis virus, and 3.98% (7/176) for pig rotavirus. The test results for the years 2019, 2020, and 2021 were counted separately, PEDV positivity rates for the years were 34.88% (15/43), 39.33% (35/89), and 36.36% (16/44), respectively. Histopathological examination revealed atrophied, broken, and detached duodenal and jejunal intestinal villi, as typical of PED, and severe congestion of the intestinal submucosa. Moreover, the results of our study clearly indicate that the G2 subtype is prevalent as the dominant strain of PEDV in Shandong Province, where its rates of morbidity and mortality continue to be high. Based on a systematic investigation and analysis of PEDV’s molecular epidemiology across Shandong Province, our results enrich current epidemiological data regarding PEDV and provide some scientific basis for preventing and controlling the disease.